A study on the extension of an upwind parallel solver for turbulent flow applications - Carlos Alberto Junqueira Branco Junior (2012)
The present work is primarily concerned with studying the influence of an upwind spatial discretization on the capability of representing turbulent flows on aerospace applications, in the context of a flow simulation code that is fairly close to a production code. Therefore, the work addresses the issues of implementing and validating an advanced turbulence model for high Reynolds number aerospace applications in the context of an existing flux-vector splitting simulation tool, which incorporates several advances in current CFD practice, including parallel processing. The flow simulation tool used in the present work was originally developed for high speed, high altitude, hypersonic applications. Hence, the code did not include any provisions for turbulence modeling, since most flows at these conditions can be adequately treated as laminar flows. Moreover, due to the presence of strong shock waves, which are typical of hypersonic applications, a very dissipative spatial discretization scheme, based on the upwind flux vector splitting concept, was employed in the construction of the inviscid numerical fluxes. Therefore, the use of such a tool for the simulation of turbulent aerospace flows requires the implementation of a turbulence closure, as well as an adequate treatment of the excessive artificial dissipation automatically generated by the original spatial discretization scheme. In the present case, the flows of interest are simulated using the three-dimensional Reynolds-averaged Navier-Stokes equations. The turbulence closure considered is the one-equation, eddy viscosity, Spalart-Allmaras model. The work discusses in detail the theoretical and numerical formulation of the selected model, as well as the validation studies. The work also demonstrates how the spatial discretization scheme is selectively modified such that the flow simulation tool remains robust for high speed applications at the same time that it can accurately compute turbulent boundary layers. Furthermore, the work also addresses the parallelization and other high performance computational issues, demonstrating that the resultant flow simulation code can achieve adequate performance on current multi-CPU, multi-core computational clusters. Finally, the work discusses issues that could be considered for the continuation of the research effort here undertaken.